Utility of bevacizumab in advanced hepatocellular carcinoma: A veterans affairs experience. (20th February 2019) - Wattenberg, Max M.; Damjanov, Nevena; Kaplan, David E.
Abstract: Hepatocellular carcinoma (HCC) is a challenging to treat malignancy with few available systemic therapies. Angiogenesis has been implicated in the pathogenesis of HCC and prior studies have suggested a role for anti‐VEGF therapy. Prior to FDA approval of second‐line therapy for advanced HCC, from 2008 until 2017, we initiated bevacizumab monotherapy (5‐10 mg/kg every 2‐3 weeks) in 12 patients with intolerance of or progression during sorafenib therapy. Bevacizumab therapy was well tolerated with only 1/12 patients experiencing a grade 3‐4 treatment‐related adverse event (transient ischemic attack) and only 2/12 patients discontinued the therapy due to adverse events. Median overall survival was 20.2 months (IQR, 7.0‐43.5), with a median time to radiologic progression of 10.4 months (IQR, 2.8‐16.1) and a disease control rate of 54%. Taken together, our experience provides rationale for further prospective investigation of bevacizumab for the treatment of advanced HCC. Abstract : Prior to FDA approval of second‐line therapy for HCC in 2017, we initiated off‐label bevacizumab monotherapy in patients with advanced HCC who had progressed on or were intolerant of sorafenib. We found a median OS of 20.2 months suggesting the need for further prospective study of bevacizumab in this disease.